Analisis Pemanfaatan Artificial Intelligence Generatif terhadap Efisiensi Proses Desain Grafis Digital pada Media Informasi Polresta Banyumas - Pratistaka 'Azmy Nurrayya; Dhanar Intan Surya Saputra (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2026)
The advancement of generative Artificial Intelligence (AI) technology has opened significant opportunities for transformation in digital graphic design production processes, including within law enforcement institutions. This study aims to analyze the influence of generative AI utilization on the efficiency of digital graphic design processes, identify supporting and inhibiting factors in its implementation, and formulate strategic recommendations for the use of generative AI in the digital information media of Polresta Banyumas. A descriptive qualitative method was employed, with data collected through observation, documentation, and literature review conducted at the Satres PPA & PPO unit of Polresta Banyumas. The AI tools examined include Canva, Adobe Firefly, and ChatGPT. The findings indicate that generative AI integration is capable of reducing design production time by up to 50–65 percent, enhancing visual consistency, and streamlining the brainstorming and content production process. However, challenges were also identified, including potential over-reliance on AI templates, diminished design originality, and the absence of formal internal policies governing AI use. This study implies that the adoption of generative AI in public institutions must be accompanied by human resource competency development and adaptive internal regulation to ensure its utilization remains optimal, responsible, and sustainable.